Pengaruh Kalsium dan Vitamin D3 Terhadap Stabilitas Tulang Alveolar - Studi pada Tikus Jantan Putih (Rattus Norvegicus) - Saifuddin Ali Anwar (MEDIA MEDIKA INDONESIANA, 2009)
The effect of calcium and vitamin D3 on alveolar bone stability - The study in white male Rattus Norvegicus rats.Background: Calsium and vitamin D3 play important roles in the development and stability of alveolar bone that hold teeth. Alveolar bone stability is very important for successful outcome of orthodontic and prostodontic treatment.Objective: This study aimed to analyze the effect of calcium and vitamin D3 supplementation on different dosages on the alveolar bone stability.Methods: A post test-only control group design experiment was carried out on white rats (Rattus norvegicus Wistar strain). The treatments were 20% calcium reduction in the diet (P1) and supplentation of 20% (P2); 40% (P3) and 60% (P4) calsium to the standar diet given to control group. Alveolar bone stability was assessed by calcium contents, the number of osteocytes and weight of alveolar bone which were measured by AAS methode, histologic examination using hematoxylin and eosin staining on two microscopic fields of lamella Haversi region of alveolar bone and weighing of upper incisivus region of alveolar bone respectively. Data were analysed using t.test, Anova and LSD. Results: There were no difference on the calcium content of the alveolar bone among the 5 experimental groups (F=0.290, p=0.881). The number of osteocytes were different among as well as between the groups (F=9.685; p=0.000). There were differences of alveolar bone weight among the groups (F=10.901; p=0.000) while the weight were only significantly increase in the groups which given 40% (P3) and 60% (P4) calcium supplements this difference was not occured in the group which given 20% calcium supplements compare to the control group. There was no difference of alveolar weight between P3 and P4 groups.Conclusions: Supplementation of calsium and vitamin D3 20%, 40% and 60% above the standard diet give different result in 2 parameters of bone stability.Keywords: Calcium, vitamin D3, alveolar bone weight.ABSTRAK Latar belakang: Kalsium dan vitamin D3 berperan dalam pembentukan dan stabilitas tulang alveolar yang berfungsi sebagai penyangga gigi. Stabilitas tulang alveolar berperan dalam keberhasilan perawatan ortodontik dan prostodontik. Penelitian ini bertujuan untuk mengkaji perbedaan pengaruh suplementasi kalsium dan vitamin D3 pada berbagai takaran terhadap stabilitas tulang alveolar pada hewan coba.Metode: Dilakukan suatu penelitian eksperimental dengan rancangan the post test-only control group, menggunakan hewan coba tikus putih jantan (Rattus norvegicus galur Wistar). Perlakuan yang diberikan berupa pengurangan kalsium 20% (P1) dan penambahan 20% (P2), 40% (P3) dan 60% (P4) kalsium dalam pakan. Stabilitas tulang alveolar dinilai dengan parameter kadar kalsium, jumlah osteosit dan berat tulang alveolar, yang secara berurutan diukur dengan metoda SSA, dihitung secara histologik dengan pengecatan hematoksilin dan eosin pada dua lapang pandang lamela Haversi regio insisivus atas dan penimbangan tulang alveolar regio incicivus atas. Data di analisis menggunakan uji t, Anova dan LSD.Hasil: Tidak ada perbedaan yang bermakna pada kadar kalsium tulang alveolar di antara 5 kelompok penelitian (F=0,290; p=0,881). Jumlah osteosit berbeda bermakna di antara kelompok dan antara kelompok perlakuan (F=9,685, p=0,000).